Stabilizing heterostructures of soft perovskite semiconductors - Wang, Yanbo; Wu, Tianhao; Barbaud, Julien; Kong, Weiyu; Cui, Danyu; Chen, Han; Yang, Xudong; Han, Liyuan (Science (American Association for the Advancement of Science), 2019)
Here we report a solution-processing strategy to stabilize the perovskite-based heterostructure. Strong Pb-Cl and Pb-O bonds formed between a [CH(NH ) ] [CH NH ] Pb I film with a Pb-rich surface and a chlorinated graphene oxide layer. The constructed heterostructure can selectively extract photogenerated charge carriers and impede the loss of decomposed components from soft perovskites, thereby reducing damage to the organic charge-transporting semiconductors. Perovskite solar cells with an aperture area of 1.02 square centimeters maintained 90% of their initial efficiency of 21% after operation at the maximum power point under AM1.5G solar light (100 milliwatts per square centimeter) at 60°C for 1000 hours. The stabilized output efficiency of the aged device was further certified by an accredited test center.